2009
DOI: 10.1002/em.20479
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity analysis of two hydroxyfuranones, byproducts of water disinfection, in human cells treated in vitro

Abstract: In general, water for human consumption is chemically disinfected, usually by adding chlorine. As well as producing safe drinking water however, the chlorine treatment, also results in a number of disinfection byproducts (DBPs). One important class of these DBPs is made up of hydroxyfuranones (HFs). In this article, we report the results of a recent investigation to assess the genotoxicity of two HFs, namely mucobromic acid (MBA) and mucochloric acid (MCA), in cultured human cells. The comet assay is used to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…2 The most common disinfection agent is chlorine, which is known to react with natural organic matter (NOM) and create disinfection by-products that are suspected to be carcinogenic. 3,4 Advanced systems of purification include ozone treatment, coagulation, activated carbon filtration, and ultra-and nano-filtration are currently employed in select municipal water systems. 2,5 These methods have many of the same difficulties, including high backpressures of small pore-sized membranes, the ability of small viruses and heavy metals to escape the system, high cost, and the requirement for a large, multistep municipal system.…”
Section: Introductionmentioning
confidence: 99%
“…2 The most common disinfection agent is chlorine, which is known to react with natural organic matter (NOM) and create disinfection by-products that are suspected to be carcinogenic. 3,4 Advanced systems of purification include ozone treatment, coagulation, activated carbon filtration, and ultra-and nano-filtration are currently employed in select municipal water systems. 2,5 These methods have many of the same difficulties, including high backpressures of small pore-sized membranes, the ability of small viruses and heavy metals to escape the system, high cost, and the requirement for a large, multistep municipal system.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies showed that MBA was able to form adducts with adenosine, to induce positive results in the Ames test, and to induce DNA damage in TK6 cells; nevertheless, it was unable to induce significant increases in the frequency of MN, neither in TK6 cells nor in cultured human lymphocytes [33,48,49]. With respect to MCA (the chlorinated hydroxyfuranone), despite its negative results in the MLA, it was reported as a direct-acting mutagen inducing chromosome damage in mammalian cells and plants, showing a high capacity to induce primary DNA damage (comet assay) in mammalian cells [33,[50][51][52].…”
Section: Discussionmentioning
confidence: 96%
“…With respect to MCA (the chlorinated hydroxyfuranone), despite its negative results in the MLA, it was reported as a direct-acting mutagen inducing chromosome damage in mammalian cells and plants, showing a high capacity to induce primary DNA damage (comet assay) in mammalian cells [33,[50][51][52].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The considerable contribution of this group of compounds to the observed mutagenicity of chlorinated tap water has received widespread attention 5, 6. Mucochloric acid (MCA, 3,4‐dichloro‐5‐hydroxyfuran‐2(5 H )‐one) and mucobromic acid (MBA, 3,4‐dibromo‐5‐hydroxyfuran‐2(5 H )‐one) are two halohydroxyfuranones that have been shown to be direct genotoxins and potential carcinogens 7–14. DNA adducts of mucohalic acids (MXA) are known, with the isolation of etheno, oxalo etheno, and halopropenal derivatives of guanosine, adenosine, and cytosine 15–22…”
Section: Introductionmentioning
confidence: 99%